Identificación del papa Pío II como autor de las "Odae in diuae dei genitricis Mariae laudes" "compiladas" por Rodrigo Fernández de Santaella. I. Fundamentos para la construcción de la hipótesis - Maestre Maestre, José María (2012)
This article establishes the basis to build the hypothesis that the Odae in diuae Dei genitricis Mariae laudes “compiled” by Rodrigo Fernández de Santaella (Sevilla, 1504) were really written by Pope Pius II. A thorough comparison of the preliminary poem and the thirteen compositions with the poem by this pontiff added as a colophon to the libellus by the Spanish humanist evidences that these “odes” were written by Pius II between 1459 and 1464 under his well-known spiritual transformation that he went through at the end of his life and because of his great devotion to Our Lady of the Assumption.
Keywords: Pío -- II, -- Papa; Fernández de Santaella, Rodrigo, -- 1444-1509